Fungsi Wacana Persuasif dalam Interaksi Jual Beli Pasar Terapung Lok Baintan Kabupaten Banjar - Achmad Akbari; Jumadi Jumadi; Sainul Hermawan (Universitas Lambung Mangkurat, 2026)
This study aims to examine persuasive discourse in buying and selling interactions at the Lok Baintan Floating Market, Banjar Regency. The focus of the research is the function of persuasive discourse in buying and selling interactions. This study uses a descriptive qualitative approach based on Aristotle's rhetorical theory, namely ethos, pathos, and logos. This approach is used to deeply understand the function of persuasive discourse that appears in buying and selling interactions naturally and contextually. Research data were obtained through direct participatory observation techniques on the communication activities of traders and buyers at the Lok Baintan Floating Market, in-depth interviews with several traders and buyers, and documentation in the form of audioand visual recordings and field notes. Research informants were selected purposively based on their active involvement in buying and selling interactions. The collected data were analyzed using the Miles and Huberman model of discourse analysis techniques, which include data reduction, data presentation, and drawing conclusions. Data validity was strengthened through triangulation using member checking. The results of the study indicate that persuasive discourse in buying and selling interactions at the floating market has functions including inviting, ordering, persuading, convincing, and giving advice. This research contributes to the study of local cultural linguistics and communication, as well as the preservation of traditional markets as cultural heritage.